21st Century Economic Transformation: The Impact of Artificial Intelligence on Markets and Employment - Loso Judijanto; Asfahani Asfahani; Arnes Yuli Vandika (Journal of Artificial Intelligence and Development, 2022)
Artificial intelligence (AI) has transformed the 21st-century economy, shaping markets and employment. This study aims to investigate the impact of AI on the market and employment. This research uses a qualitative approach, which takes data through observation and interview techniques. In contrast, the data analysis technique uses the Miles Humbermen model through data presentation, reduction, and conclusion. This research reveals that although AI increases efficiency and productivity, it also causes job displacement and requires upskilling efforts and new skills. Additionally, AI drives the emergence of new sectors and raises ethical and regulatory challenges that must be overcome for sustainable economic development.